Comparison of the Effectiveness of Integrated Behavioral Couple Therapy and Schema-Focused Couple Therapy on Conflict Resolution Styles in Conflicting Couples - Kordavani, Shokoufeh; Khaleghipour, Shahnaz; Tabatabaeinejad, Fatemeh (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to compare the effectiveness of integrated behavioral couple therapy and schema-focused couple therapy on conflict resolution styles among conflicting couples in Shiraz. Methods: The research employed a quasi-experimental design with pre-test, post-test, and one-month follow-up. The statistical population included all conflicting couples who visited the Fajr Counseling Center in Shiraz in 2022, from whom 45 couples were selected through convenience sampling and randomly assigned to three groups: integrated behavioral couple therapy, schema-focused couple therapy, and a control group. The Rahim Conflict Resolution Styles Questionnaire was used as the measurement tool. Experimental group one underwent a 16-session program of integrated behavioral couple therapy, and experimental group two a 13-session program of schema-focused couple therapy, while the control group was placed on a waiting list. Data were analyzed using repeated measures analysis of variance. Findings: Results indicated that both interventions, integrated behavioral couple therapy and schema-focused couple therapy, were effective in addressing conflict resolution styles. There was a difference in the effectiveness of integrated behavioral couple therapy and schema-focused couple therapy on conflict resolution styles. Conclusion: Based on the findings, both treatments are effective for couples’ conflict resolution styles, but the effectiveness of integrated behavioral couple therapy is reported to be more effective.